Les compétences de l’État riverain au delà de la mer territoriale - Jean‑Pierre Beurier (Bulletin de l’Association de Géographes Français, 2013)
The territorial sea is considered, with some reservations, as a sovereign territory of the coastal State. The exclusive economic zone and the continental shelf, when it exceeds the latter, are defined in the light of economic competencies. The High sea is an area of freedom with only the law of the Flag, with few exceptions, defined in the present paper.